Proteomic dissection of the Arabidopsis Golgi and trans-Golgi network - Parsons, Harriet T.; Drakakaki, Georgia; Heazlewood, Joshua L. (Frontiers in Plant Science, 2013)
The plant Golgi apparatus and trans-Golgi network are major functional hubs within the plant cell and are involved in a diverse and vital series of functions to maintain plant growth and development. Recently, a series of disparate technical approaches have been used to isolate and characterize components of these complex organelles by mass spectrometry in the model plant Arabidopsis thaliana. Collectively, these studies have increased the number of Golgi and vesicular localized proteins identified by mass spectrometry to nearly 500 proteins. We have sought to provide a brief overview of these technical approaches and bring the datasets together to examine how they can reveal insights into the secretory pathway.